Communicating Subjective Evaluations - Matthias Lang (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Consider managers evaluating their employeesṕerformances. Should managers justify their subjective evaluations? Suppose a managerś evaluation is private information. Justifying her evaluation is costly but limits the principalś scope for distorting her evaluation of the employee. I show that the manager justifies her evaluation if and only if the employeeś performance was poor. The justification assures the employee that the manager has not distorted the evaluation downwards. For good performance, however, the manager pays a constant high wage without justification. The empirical literature demonstrates that subjective evaluations are lenient and discriminate poorly between good performance levels. This pattern was attributed to biased managers. I show that these effects occur in optimal contracts without any biased behavior.
Keywords: D82; D86; J41; M52; 330; communication; justification; subjective evaluation; centrality; leniency; disclosure